Regulation of type I-interferon responses in the human epidermal melanocyte cell line SKMEL infected by the Ross River alphavirus. Issue 2 (December 2015) - Assi, Mohamad; Thon-Hon, Vincent Gérard; Jaffar-Bandjee, Marie-Christine; Martinez, Audrey; Gasque, Philippe
Graphical abstract: Highlights: RRV alphavirus infection at the skin level can cause rash, lesions and depigmentation. RRV infects SKMEL human melanocyte cell line and leading to cytopathic activities. Infected cells do not commit to canonical apoptosis. A delayed and altered innate immune antiviral response is observed. Melanocytes may be a sanctuary for RRV and other alphaviruses. Abstract: Melanocytes are melanin-producing cells and with emerging innate immune functions including the expression of antiviral interferon-type I cytokines. We herein ascertained the susceptibility of the human melanocytes to Ross River alphavirus (RRV) infection and analyzed the subsequent immune responses. We demonstrated for the first time that (1) SKMEL-28 melanocyte cell line was susceptible to RRV infection and displaying major cytopathic activities and (2) RRV interfered with the interferon-type I response by altering nuclear translocation of pSTAT1 and pSTAT2 in infected SKMEL-28. These results suggest that the human melanoma cell line SKMEL-28 is a valuable model to analyze the mechanisms involved in severe skin manifestations and melanocyte's immunity at the portal of entry of major infection by arboviruses.